Neutrophilic Dermatosis of the Dorsal Hands: Report of a Case and Review of the Literature - Narciss Mobini; Kaviyon Sadrolashrafi; Susun Michaels (Hindawi Limited, 2019)
Neutrophilic dermatosis of the dorsal hands is an underrecognized entity, which is a distributional variant of Sweet's syndrome. It is often clinically misdiagnosed as an infectious process in overwhelming majority of the cases and the treatment is therefore delayed. Also, its association with underlying systemic and neoplastic disorders makes the need for an accurate diagnosis more crucial. We present a 45-year-old Caucasian woman who was initially diagnosed as having a hand infection with unsuccessful courses of antibiotic therapy. A later biopsy revealed a diffuse dermal infiltrate of neutrophils with leukocytoclasis, vasculopathic changes, and marked papillary dermal edema. Patient responded rapidly to oral prednisone treatment. By sharing a new case and comprehensive review of available published literature, we intend to raise awareness of this underreported entity and emphasize the role of timely biopsy of the lesions that will not only lead to an accurate diagnosis, but also avoid unnecessary antibiotic treatments, potentially aggressive management strategies such as surgical debridement or amputation, and referrals to wound care centers. More importantly, it will prompt a search to exclude any possible association, particularly hematopoietic malignancies.